(untitled) (Práxis Educativa, 2025)
Data from the 2024 School Census indicate that 92.6% of enrollments of students in Special Education in Basic Education are concentrated in mainstream schools. Despite some progress, many challenges remain, including ensuring support in resource rooms for Specialized Educational Service (SES) and access to the curriculum, especially for students with intellectual disabilities and Autism Spectrum Disorder (ASD). To contribute to the debate in this field, this article discusses the relevance of the teaching case for inclusive educational planning, with an emphasis on students with disabilities who have complex communication needs. This is a qualitative study with a collaborative approach, conducted in three public schools in the Baixada Fluminense region, in the state of Rio de Janeiro, Brazil, between April and December 2024, involving teachers, their students, and the students’ mothers. The collaborative nature of the study was present throughout all stages of the investigation, with active listening to those involved, joint construction of reflections, and appreciation of participants’ experiences. The results highlight the importance of the teaching case for understanding the educational process and for planning interventions using Assistive Technology (AT) and Augmentative and Alternative Communication (AAC). The involvement of mothers and their relationship with the school also proved to be fundamental in their children’s educational process. Keywords: Teaching case. Inclusive education. Augmentative and Alternative Communication. Complex communication needs. Assistive Technology.